Análise da resistência à fadiga de tubos de aço API 5CT N80 Tipo Q soldados via processo de indução magnética de alta frequência (HFIW) - Sorrija, Bruno Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Steel pipes, used in the oil and gas industry in prospection and exploration activities, are often subjected to cyclic loading during their transportation (transit fatigue) and during their service life. Considering this, these steel pipes must have excellent structural integrity in order to avoid premature failure by fatigue mechanisms. However, the HFIW manufacturing process, widely used by the industry, involves mechanical forming and welding and, therefore, defects are inherently present in the finished products, remarkably an interface between the edges of the steel sheets that are welded into tubes. In this work it has been investigated how the HFIW manufacturing process can reduce the fatigue resistance of API 5CT N80 type Q steel tubes and lead to a mechanical anisotropy of the finished product. To keep the specimens characteristics closer to the real steel pipes, axial fatigue tests have been performed with round specimens which had their thickness equal to the thickness of the walls of the pipes from which they had been taken from. It has been developed also a device and a method to test small length sections of steel tubes, which have shown potential to be used in the future as a new methodology for the study of fatigue in steel pipes. The results of the axial fatigue tests (carried out to compare the welded joint to a position situated 90° from it) indicate that the welded joint can act as a stress raiser and contributes to reduce the fatigue resistance of the steel pipes, in a inversely proportional relationship with the increasing of the applied dynamic loading. It has been observed also that some defects, which result from the manufacturing process, can act as points for the nucleation of fatigue cracks and, for this, they should not be present in the manufactured product. Tensile tests, metallographic analysis, fractography study and microhardness tests had been carried out to complement the fatigue tests results.

Tubos de aço utilizados na exploração e prospecção de petróleo e gás natural estão sujeitos a carregamentos dinâmicos durante o transporte (transit fatigue) e também quando em serviço. Por este motivo é imperativo que os tubos utilizados apresentem excelente integridade estrutural a fim de evitar a ocorrência de falhas prematuras devido à fadiga. Contudo, como o processo de fabricação HFIW, largamente utilizado pela indústria, envolve conformação mecânica seguida de soldagem, defeitos estarão inerentemente presentes nos tubos, notadamente uma interface entre as bordas das chapas soldadas. No presente trabalho foi investigado como a junta soldada de tubos de aço API 5CT N80 tipo Q pode contribuir para redução da vida em fadiga e como o processo como um todo pode levar a anisotropia mecânica dos tubos. Para preservar ao máximo as características originais dos tubos foram realizados ensaios de fadiga axiais utilizando corpos de prova não previstos pelas normas técnicas vigentes, com espessuras iguais as das paredes dos tubos dos quais foram retirados. Foi também desenvolvido e testado um dispositivo para realização de ensaios de fadiga utilizando trechos de tubo, o qual mostrou potencial para a realização de ensaios futuros. Os resultados dos ensaios axiais (realizados de modo a comparar a região da junta soldada como uma posição a 90° dela) indicaram que a junta soldada pode agir como um tipo de concentrador de tensões, contribuindo para a diminuição da resistência à fadiga dos tubos de maneira inversamente proporcional à carga aplicada. Também foi observado que defeitos resultantes do processo de fabricação (muitos deles macroscópicos) podem atuar como pontos para a nucleação de trincas de fadiga e que, portanto, não deveriam estar presentes no produto final. Ensaios de tração, análises metalográfias, fractográficas e de microdureza também foram realizados de modo a complementar os resultados dos ensaios de fadiga.
Fatigue analysis of API 5CT N80 Q Steel Pipes manufactured by High Frequency Induction Welding (HFIW)
Keywords: API 5CT N80 type Q Steel; HFIW steel pipe manufacturing proccess; New methods for studying fatigue in steel pipes; HFIW welded joint structural integrity; Aço API 5CT N80 tipo Q; Fabricação de tubos via HFIW; Novos métodos para o estudo de fadiga em tubos; Integridade estrutural de junta soldada via HFIW